2012
DOI: 10.2136/sssaj2011.0175
|View full text |Cite
|
Sign up to set email alerts
|

Soil Tests as Risk Indicators for Leaching of Dissolved Phosphorus from Agricultural Soils in Ontario

Abstract: Phosphorus movement in subsurface flow from agricultural soils can be a significant pathway contributing to eutrophication of surface waters. Our study aimed to evaluate several environmental and agronomic soil P tests as indicators of dissolved reactive P (DRP) concentrations in soil-column leachate from Ontario soils. Undisturbed soil columns were collected from six major soil series, with 10 sites of each to quantitatively cover a wide range of soil test P (STP) or degree of P saturation (DPS). Split-line m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 37 publications
5
60
0
Order By: Relevance
“…Ashjaei et al (2010) observed a strong correlation between labile Pi forms and leachate Pi concentrations; however, in their study, higher manure application rates were used and correlations were only significant when the soil labile Pi fractions exceeded 40 mg kg −1 . Although lower labile Pi (Resin and Bicarb) measures in the soil with reduced P inputs may be indicative of a decreased risk of soluble soil P losses in leaching waters, given the STP levels in our study and the work by Wang et al (2010Wang et al ( , 2012, the impact on soil P loss would be very small. The relatively less labile NaOH-Pi fraction was not significantly influenced by P source, rate, or P source × rate interaction (Table 3).…”
Section: Soil Inorganic and Organic Phosphorusmentioning
confidence: 70%
See 1 more Smart Citation
“…Ashjaei et al (2010) observed a strong correlation between labile Pi forms and leachate Pi concentrations; however, in their study, higher manure application rates were used and correlations were only significant when the soil labile Pi fractions exceeded 40 mg kg −1 . Although lower labile Pi (Resin and Bicarb) measures in the soil with reduced P inputs may be indicative of a decreased risk of soluble soil P losses in leaching waters, given the STP levels in our study and the work by Wang et al (2010Wang et al ( , 2012, the impact on soil P loss would be very small. The relatively less labile NaOH-Pi fraction was not significantly influenced by P source, rate, or P source × rate interaction (Table 3).…”
Section: Soil Inorganic and Organic Phosphorusmentioning
confidence: 70%
“…As a consequence, manure applications based on crop N requirements often apply P in excess of crop requirements, leading to soil P accumulation. Increased soil test P (STP) levels may indicate an increased risk of P loss through runoff and leaching, particularly when soil levels are near or exceed agronomic requirements (Wang et al 2010(Wang et al , 2012. Throughout many regions of the world, eutrophication is becoming a growing environmental concern, with agriculture identified as a major contributor of P to surface waters (Smith et al 2007;Withers et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, recommendations for P fertilizers are based on soil test methods and recently they were also used for environmental risk assessment Sharpley et al, 2003;Daly et al, 2015). It was indicated that the P extracted by extractants such as Olsen-P and Mehlich-3-P had correlated well with P loss via runoff and/or leaching (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, a routine method for assessing P leaching from soil profiles is difficult to achieve because the process is time consuming and labor intensive (Heckrath et al, 1995; Hesketh and Brookes, 2000). An alternative method is to determine the leachable P content in topsoil by using H 2 O and 0.01 M CaCl 2 to evaluate the potential of P leaching from topsoil (Heckrath et al, 1995; Hesketh and Brookes, 2000; Wang et al, 2012). An indicator for P leaching based on the change‐point estimated with the split‐line model between Olsen P and leachable P has been used to predict the risk of P leaching in topsoil (Hesketh and Brookes, 2000; Zhao et al, 2007; Li et al, 2015; Jalali and Jalali, 2017).…”
mentioning
confidence: 99%